Mammal Distribution and Diversity in the Protected Forest of RPH Sumbermanjing Kulon KPH Malang - Nirmala Ayu Aryanti; Dany Fiqrullah Jaki; Teguh Pribadi; Iwan Kurniawan (Jurnal Penelitian Hutan dan Konservasi Alam, 2021)
The Protected Forest of RPH (Forest Management Resort) Sumbermanjing Kulon is an area, which is susceptible to land conversion due to human activities, such as road construction and tourism. These conditions might harm the habitat of several animals and disturb their movements, specifically in the mammal group. Therefore, the purpose of this research is to determine the distribution and diversity of mammals as the basis for the proper management of the RPH. This research was conducted on a variety of forest habitats located on plot 97A, which covers an area of 331.5 Ha. Moreover, data were collected by creating line transects in this location and then analyzed by constructing a map of the mammals' distribution using the Shannon-Winer diversity index, evenness, and species richness. According to the results, 23 species of mammals were scattered in three types of habitats. The low category of mammal species diversity index was discovered in the mangrove forest (0.69), while the tropical rainforest (2.48) and coastal forest (2.18 were moderate). Furthermore, the mammal species evenness index in the lowland tropical rainforest, mangrove, and coastal forests indicated relatively even results while the highest mammal species richness index was detected in the lowland tropical rainforest. The mammal diversity results can be used by area managers for sustainable management.